INDICATORS OF RESEARCHERS’ DIGITAL COMPETENCE IN THE CONTEXT OF WEB-BASED ENCYCLOPEDIC RESOURCE USE (Journal of Information Technologies in Education (ITE), 2025)
The study addresses the issue of identifying indicators of digital competence (DC) among researchers in the context of using web-based encyclopedic resources (WBER) as elements of digital academic infrastructure. The focus is placed on the role of WBER as a platform of open science, which introduces new requirements for researchers' digital preparedness, particularly about working with ontologically structured data, metadata, semantic web services, and editorial standards of digital environments.The author's contribution to the problem lies in refining the list of relevant DC indicators for researchers through adapting the DigComp 2.2 framework to the needs of the academic environment. These indicators are classified according to the traditional three-component model: knowledge (of WBER structures and functions, principles of the semantic web, and digital publishing standards), skills (content analysis, source verification, editing, integration of WBER into research activities, and collaborative data work), and attitudes (participation in content development, adherence to systemic coherence, and academic citation practices).The key methodological approach is the principle of internal consistency, applied to assess the alignment of three models of structuring digital competence with the goals and objectives of the study, namely, the functional-operational, the contextual-integrative, and the structural-competency-based approaches. The latter is the most relevant, as it enables the construction of a system of measurable indicators that can be replicated, adapted to evaluation methodologies, and, if necessary, integrated into training and professional development systems.The practical foundation of the study is based on the experience of the "Ukrainian Electronic Encyclopedia of Education" platform, particularly the analysis of user activities (authors, editors, and moderators) related to content creation, editing, updating, and categorization
Keywords: digital competence; researchers; web-based information systems; online encyclopedia; electronic scientific and educational resource; users of the